Prephiral Bacterial Infectious Agent triggers Neuroinflammatory Responses and Neurobehavioral Impairment in Wild-Type Mice - Atalah, Hadeer (AUC Knowledge Fountain, 2026)
Neurodegenerative diseases, including Alzheimer's and Parkinson's, present an increasing global challenge, with chronic neuroinflammation identified as a principal factor alongside genetic, environmental, and infectious influences (Boyd et al., 2022).  Epidemiological data associate bacterial infections with a 40% heightened risk of Parkinson's disease; however, the mechanisms—especially the direct connection between peripheral sepsis and the silent onset of central nervous system pathology absent acute meningitis—are inadequately investigated (Smeyne et al., 2021), particularly concerning common pathogens like Klebsiella pneumoniae in high-burden areas such as Egyptian ICUs, where it constitutes 30% of cases (Alkompoz et al., 2023). This study filled the gap by creating a preclinical model in wild-type C57BL/6 mice to examine if peripheral K. pneumoniae infection triggers neuroinflammatory responses and neurobehavioral deficits and whether post-sepsis antibiotics alleviate these effects. Forty female mice were randomly assigned to four groups: infected (10^6 CFU intraperitoneally), infected with ampicillin (48-hour delay followed by 7 days of oral administration), ampicillin-only, and untreated controls. At six weeks post-infection, behavioral assays evaluated anxiety, depression, memory, and motor coordination/Parkinsonian symptoms; brains were subjected to histological analysis (H&E, immunohistochemistry) and qRT-PCR for eleven neuroinflammatory, apoptotic, and oxidative stress genes (e.g., IL-1β, iba1, IL-6, Casp3, HO-1, and nNOS). Infected mice displayed anxiety-like behaviors in a dose-dependent manner (increased peripheral time, immobility), memory deficits (decreased recognition index), and motor impairments (extended pole descent, beam slips, asymmetric forelimb usage; all p < 0.05 compared to controls by ANOVA). Molecular analyses demonstrated elevated levels of pro-inflammatory cytokines (IL-1β, IL-6, iba1), markers of oxidative stress (nNOS, HO-1), and pro-apoptotic changes (Casp3/Bax↑, Bcl2↓), alongside histological confirmation of glial activation and neuronal loss. Antibiotic treatment protocol has mitigated the deficits caused by the systemic infection but has resulted in persistent, non-significant HO-1 elevation, suggesting a partial neuroprotective role. This groundbreaking study demonstrates, for the first time in blank wild-type models, that peripheral K. pneumoniae infection endures glial activation, neuroinflammation, CNS morphological alterations, and complex behavioral impairment, resembling post-sepsis encephalopathy. The findings highlight the limitations of antibiotic stewardship by identifying infection as a modifiable environmental risk and emphasizing the urgent necessity for supplementary anti-inflammatory or antioxidant therapies. The implications for public health are significant: improved sepsis protocols in at-risk populations may prevent neurodegeneration, reduce morbidity among survivors, and inform targeted interventions for cytokine storms and gut-brain/lung-brain interactions, potentially transforming the prevention of neurodegenerative diseases.